Improving teacher : Development Evaluation ; A Guide for Leaders, Coaches, & Teachers. - Marzano, Robert J.; Rains, Cameron L.; Warrick, Philip B.; Simms, Julia A. (Marzano Resourses, 2021)
Teachers cannot become great unless they are given the time, support, and tools to grow in their professional practice. Written for teachers, coaches, and educational leaders, this resource offers a paradigm-shifting approach to teacher development and evaluation. The authors share research-backed steps for improvement, outline the principles for successful observation, and offer extensive protocols designed to help readers fully implement the book’s recommendations.